2001
DOI: 10.1001/archotol.127.8.991
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Transplantation and Replantation of the Rabbit Submandibular Gland

Abstract: The rabbit submandibular gland is able to undergo microvascular transplantation and replantation with evidence of long-term survivability and preserved function. The body's natural response to surgery and tissue transplantation makes replantation a technical challenge; however, methods delineated herein alleviate many of the potential pitfalls. Extending these results to humans, patients who are to undergo radiation therapy could have a disease-free gland removed from the neck, transferred outside of the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
(27 reference statements)
1
13
0
1
Order By: Relevance
“…As previously demonstrated in an experimental series [28,29] and in a clinical setting, in patients with severe keratoconjunctivitis [21][22][23][24]26] where one gland was transplanted to the temporal region and the submandibular duct connected to the lateral conjunctival fornix, this denervation had no detrimental effect on basic saliva production. The idea of performing a two-stage autotransplantation of one submandibular gland to treat postradiotherapeutic xerostomia, as originally proposed by Spiegel et al [27,28,29], appeared to be a surgical approach with an acceptable perioperative risk in relation to the expected benefit. In order to keep the necessary operative intervention as low as possible, the first series was limited to HNSCC patients where standard therapy included the use of a free radial forearm flap (RFF).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…As previously demonstrated in an experimental series [28,29] and in a clinical setting, in patients with severe keratoconjunctivitis [21][22][23][24]26] where one gland was transplanted to the temporal region and the submandibular duct connected to the lateral conjunctival fornix, this denervation had no detrimental effect on basic saliva production. The idea of performing a two-stage autotransplantation of one submandibular gland to treat postradiotherapeutic xerostomia, as originally proposed by Spiegel et al [27,28,29], appeared to be a surgical approach with an acceptable perioperative risk in relation to the expected benefit. In order to keep the necessary operative intervention as low as possible, the first series was limited to HNSCC patients where standard therapy included the use of a free radial forearm flap (RFF).…”
Section: Discussionsupporting
confidence: 62%
“…The additional risk of transplantation failure, which is estimated in the literature at a level of 5 % for each surgical step [21,24,28], was higher in this study group (27 %). This is due to a training curve since the venous insufficiency only occurred in the first patients after the first surgical step.…”
Section: Discussionmentioning
confidence: 52%
“…3). Twenty-three patients revealed a pathology in the submandibular gland; chronical sialadenitis (12), atrophy (5), tumor infiltration (5) and intraglandular lymph node (1) (Fig. 4).…”
Section: Overview Of All Patients That Underwent Neck Dissectionmentioning
confidence: 99%
“…Spiegel et al 12 showed that the submandibular gland is involved only in cases of ipsilateral oral cavity tumors. Perivascular-submandibular lymph node metastasis in squamous cell carcinoma of the tongue and floor of mouth seems to have a small incidence.…”
mentioning
confidence: 99%
“…Of course, by remaining pedicled, the authors needed to be very careful in modifying the radiation field to avoid the gland, and they therefore limit the situations in which this technique can be applied. Spiegel et al 13 demonstrated that it is possible to transplant the submandibular gland to the groin area in rabbits and to transfer it back to the neck area with the gland maintaining its integrity and function. They propose that this is a promising preventive treatment for xerostomia in patients with head and neck cancers about to undergo radiation therapy.…”
Section: -1068 2004mentioning
confidence: 99%